An Innovative Direct NF-FF Transformation Technique with Helicoidal Scanning - Francesco D’Agostino; Flaminio Ferrara; Claudio Gennarelli; Rocco Guerriero; Massimo Migliozzi (International Journal of Antennas and Propagation)
A direct near-field-far-field transformation with helicoidal scanning is developed. It is based on the nonredundant sampling representation of electromagnetic fields and uses a spherical antenna modelling to determine the number of helix turns. Moreover, the number of voltage samples on each of them is fixed by the maximum transverse dimension of the antenna, both to simplify the mechanical scanning and to reduce the computational effort. This technique allows the evaluation of the antenna far field directly from a minimum set of near-field data without interpolating them. Although the number of near-field data employed by the developed technique is slightly increased with respect to that required by rigorously applying the nonredundant sampling representation on the helix, it is still remarkably smaller than that needed by the standard near-field-far-field transformation with cylindrical scanning. The effectiveness of the technique is assessed by numerical and experimental results.